Answer:
The price of the jacket was $31.43
Step-by-step explanation:
Let the cost of a jacket = x
Let the cost of a pair of pants = y
Such that,
x + y = $66.12.........Equation 1.
From the conditional statement,
x = y - $3.26..........Equation 2.
Solve both equations simultaneously, using the substitution method
From Equation 2;
x = y - 3.26
Substitute y - 3.26 for x in Equation 1.
x + y = 66.12, now becomes,
y - 3.26 + y = 66.12
collect like terms
y + y = 66.12 + 3.26
2y = 69.36
y= 69.36/2 = $34.69.
Put y = $34.69 in Equation 2. to obtain x
x = 34.69 - 3.26
x = $31.43